ANALISIS BEBAN KERJA MENTAL OPERATOR PRODUKSI NASA-TLX DAN RSME PADA PT XYZ - Afator, Azyumardi Arrozikiy; Hazim, Hazim (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
In today's competitive industrial world, many companies engaged in manufacturing are faced with pressure to maintain employee welfare along with high productivity. This research aims to analyze the problems often faced by employees in facing challenges in the industrial world. The topic of this research is mental workload, where mental workload is all activities carried out involving the use of the brain to think. This research uses the NASA TLX and RSME methods applied to employees of the Liquid Production Department at PT XYZ. This study shows that employees at PT XYZ, fall into the Very High category with an average WWL value of 79.41. Then based on the RSME method, the average value of effort is 90.58 which is included in the category of great effort. So it is necessary to evaluate or improve work, as well as review tasks related to obligations and authority, to the work area for workers at PT XYZ.